2011
DOI: 10.1148/radiol.11102234
|View full text |Cite
|
Sign up to set email alerts
|

Knee Cartilage T2 Characteristics and Evolution in Relation to Morphologic Abnormalities Detected at 3-T MR Imaging: A Longitudinal Study of the Normal Control Cohort from the Osteoarthritis Initiative

Abstract: Purpose:To determine the frequency of degenerative knee morphologic abnormalities in asymptomatic individuals by using 3-T magnetic resonance (MR) imaging and to investigate the characteristics and evolution of cartilage T2 values in relation to morphologic abnormalities with a longitudinal study. Materials and Methods:The study was approved by the institutional review board and was compliant with HIPAA. Ninety-fi ve asymptomatic subjects aged 45-78 years who were free of risk factors for osteoarthritis (OA) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 31 publications
10
74
2
Order By: Relevance
“…Intra-class correlation coefficients (ICCs) were calculated in order to compare each WORMS subscore (cartilage, meniscus, BMEP) separately. Excellent intra-and inter-reader reproducibility of WORMS grading by our group has also been validated in previous studies [31][32][33].…”
Section: Reproducibilitysupporting
confidence: 78%
“…Intra-class correlation coefficients (ICCs) were calculated in order to compare each WORMS subscore (cartilage, meniscus, BMEP) separately. Excellent intra-and inter-reader reproducibility of WORMS grading by our group has also been validated in previous studies [31][32][33].…”
Section: Reproducibilitysupporting
confidence: 78%
“…4, baseline iw-coronal MR obtained in a 56-year-old male (a) demonstrates medial femoral condyle insufficiency fracture (arrow), while follow-up MR obtained 5 months later (b) demonstrates interval healing. Incidentally shown is a small enchondroma in the lateral femoral condyle previously published study reporting the frequency of any BMEP in knee MR exams performed in healthy normal adults as 36 % [36]. The previously described rates of cartilage loss and meniscal lesions in normal control populations, reported as 1.0-5.3 and 40 %, respectively, was also significantly less than the frequencies of these lesions in our study cohort (75.7 and 94.1 %, respectively) [36].…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, despite correlations that show a difference in these qMRI measures between normal and damaged cartilage, there may be a lack of sensitivity in distinguishing the levels of clinical damage [37,90,124,125]. Finally, among the studies examined herein, even studies that have shown a significant difference in T 2 , dGEMRIC or T 1r values between normal cartilage and varying degrees of cartilage damage require anywhere from just two to four samples [57] to 95 samples [36] per group, depending on the specific study [33,49,55].…”
Section: Current Limitations Of Quantitative Magnetic Resonance Imagimentioning
confidence: 91%